The Integration of Modern Legal Systems (on an Example of American Law) - David Tonievich Karamanukyan (Сибирское юридическое обозрение, 2011)
In this article a comparative analysis is given of the specific attributes of the American and common law legal systems. Considered traditionally as part of common law legal system, the Author investigates distinctive attributes of American law, proving the fact of integration of significant features of Continental Europe and Anglo-Saxon legal systems.